The use of mobile phones for demographic surveillance of mobile pastoralists and their animals in Chad: proof of principle - Vreni Jean-Richard; Lisa Crump; Doumagoum Moto Daugla; Jan Hattendorf; Esther Schelling; Jakob Zinsstag (Global Health Action, 2014)
Background: Demographic information is foundational for the planning and management of social programmes, in particular health services. The existing INDEPTH network surveillance sites are limited to coverage of sedentary populations. Including mobile populations in this approach would be expensive, time consuming and possibly low in accuracy. Very little is known about the demography of mobile pastoralists and their animals, so innovative approaches are urgently needed. Objective: To test and evaluate a mobile demographic surveillance system for mobile pastoralist households, including livestock herds, using mobile phones. Design: Mobile pastoralist camps were monitored (10 for 12 months and 10 for 18 months) using biweekly mobile phone calls with camp leaders and their wives to conduct interviews about the households and livestock. The collected information was validated through personal visits, GPS data and a livestock demographic model. Results: The study showed the feasibility of mobile phone surveillance for mobile pastoralist camps, providing usable, valid information on human and livestock population structures, pregnancy outcomes and herd dynamics, as well as migration patterns. The approach was low-cost and applicable with the existing local resources. Conclusion: Demographic surveillance in mobile populations is feasible using mobile phones. Expansion of the small-scale system into a full mobile demographic surveillance system is warranted and would likely lead to improved planning and provision of human and animal health care.